2008
DOI: 10.1097/cad.0b013e3282f28842
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical antitumor efficacy evaluation of dendrimer-based methotrexate conjugates

Abstract: Our previous studies have demonstrated the in-vitro and in-vivo targeting of a generation-5 (G5) dendrimer-based multifunctional conjugate, which used folic acid (FA) as the targeting agent and methotrexate (MTX) as the chemotherapeutic drug. For the synthesized G5-FA-MTX nanodevice conjugate to be clinically applicable as a cancer therapeutic drug, it is important that the compound elicits cytotoxicity specifically and consistently. The aim of this work was to evaluate four independently synthesized batches o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 25 publications
2
37
0
Order By: Relevance
“…It is reported that conjugation of dendrimers with biological targeting moieties such as FA can significantly increase their specific function on tumor cells in vitro (using KB cells) [132] (Table 4). The selective in vitro cytotoxicity of FA-conjugated methotrexate-loaded dendrimers against tumor cells confirms former report [133]. Kesharwani et al have recently analyzed the anti-tumor potential of different generations of FA-targeted Melphalanloaded poly(propyleneimine) (PPI) dendrimers both in vitro (MCF-7 cells) and in vivo.…”
Section: Dendrimerssupporting
confidence: 66%
“…It is reported that conjugation of dendrimers with biological targeting moieties such as FA can significantly increase their specific function on tumor cells in vitro (using KB cells) [132] (Table 4). The selective in vitro cytotoxicity of FA-conjugated methotrexate-loaded dendrimers against tumor cells confirms former report [133]. Kesharwani et al have recently analyzed the anti-tumor potential of different generations of FA-targeted Melphalanloaded poly(propyleneimine) (PPI) dendrimers both in vitro (MCF-7 cells) and in vivo.…”
Section: Dendrimerssupporting
confidence: 66%
“…3 4 Several reports indicated that anticancer drugs (camptothecin, 6-mercaptopurin, methotrexate, adriamycin, 5-fluorouracil, and paclitaxel) were encapsulated into the PAMAM dendrimer exhibiting a significant enhancement of its water solubility, storage stability, and anti-tumor activity. [5][6][7][8][9][10] However, there are a few disadvantages accompanied with PAMAM dendrimer drug-delivery system including hemolytic toxicity and cell lysis due to a strong interaction of the positively charged dendrimer and the negatively charged cell membrane resulting in membrane disruption. 9 11-13 Like other cationic polymers such as polylysine and poly(ethyleneimine), these disadvantages have been solved by conjugating biocompatible and hydrophilic polymers into amine group-terminated dendrimer.…”
Section: Introductionmentioning
confidence: 99%
“…mercaptopurin, methotrexate, 5-FU, and paclitaxel) were encapsulated into the PAMAM dendrimer exhibiting a significant enhancement of its water solubility, storage stability, reduction of side-effects, and anti-tumor activity [17][18][19][20][21]. However, there are a few disadvantages accompanied with the amine-terminated dendrimer-based carriers including hemolytic toxicity and cell lysis due to a strong interaction of its positively charge and a negative charge on cell membrane resulting in disruption of the cellular membrane [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%